New Insights in Central Venous Disorders. The Role of Transvenous Lead Extractions - Domenichini, Giulia; Le Bloa, Mathieu; Carroz, Patrice; Graf, Denis; Herrera-Siklody, Claudia; Teres, Cheryl; Porretta, Alessandra Pia; Pascale, Patrizio; Pruvot, Etienne (Frontiers in Cardiovascular Medicine, 2022)
Over the last decades, the implementation of new technology in cardiac pacemakers and defibrillators as well as the increasing life expectancy have been associated with a higher incidence of transvenous lead complications over time. Variable degrees of venous stenosis at the level of the subclavian vein, the innominate trunk and the superior vena cava are reported in up to 50% of implanted patients. Importantly, the number of implanted leads seems to be the main risk factor for such complications. Extraction of abandoned or dysfunctional leads is a potential solution to overcome venous stenosis in case of device upgrades requiring additional leads, but also, in addition to venous angioplasty and stenting, to reduce symptoms related to the venous stenosis itself, i.e. the superior vena cava syndrome. This review explores the role of transvenous lead extraction procedures as therapeutical option in case of central venous disorders related to transvenous cardiac leads. We also describe the different extraction techniques available and other clinical indications for lead extractions such as lead infections. Finally, we discuss the alternative therapeutic options for cardiac stimulation or defibrillation in case of chronic venous occlusions that preclude the implant of conventional transvenous cardiac devices.